The Gambia : 2008 Article IV Consultation and Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report ;, 2008)
The Gambia's 2008 Article IV Consultation and Third Review Under the Poverty Reduction and Growth Facility are discussed. A sharp appreciation of the dalasi in 2007 has mitigated the impact of increases in world food and oil prices. The authorities' response to the continuing rise in these world prices has been measured; while eliminating sales tax on the rise, they have raised other taxes to compensate for the revenue loss. Petroleum product prices have been adjusted to eliminate an implicit subsidy and bring them in line with import costs.